IDENTIFIKASI KESULITAN MENGERJAKAN SOAL FISIKA SISWA KELAS VIII SMP IT INSAN MULIA BATANGHARI PADA MATERI GETARAN DAN GELOMBANG TAHUN AJARAN 2017/2018 - Khairani, Luthfi; Partono, Partono; Alarifin, Dedy Hidayatullah (JURNAL FIRNAS, 2021)
Abstract: This research was conducted to identify the difficulties of working onphysics problems in the junior high school of the students based on the problemsolving stages. This study uses test and interview methods, for respondentsconsist of 19 students in the eighth grade of SMP It Insan Mulia Batanghari. Theresults showed that the average difficulty at the stage of writing down the knownand asked quantities was 47.93%, writing the formula/equation used was63.16%, operating arithmetic of 85.34%, and writing the final unit of 31.98 %.Forms of difficulty experienced by the students include writing symbols,converting units, writing formulas, performing calculations, and writing down thefinal units.Keywords: Identify, Trouble Working on Questions, Physics Problem Solving